Experimental Study on CFRP-Confined Circularized Concrete-Filled Square Steel Tube Short Columns - Yuchuan Wen; Zhongjun Hu; Anningjing Li; Quanheng Li; Xuepeng Li; Yan Xu (Advances in Materials Science and Engineering)
This study investigates the suitability of the circularization technique for strengthening square concrete-filled square steel tube (CFSST) short columns. A total of 16 specimens were tested under axial compression. The main parameters under investigation were concrete strength, the thickness of arc cement mortar layer components (CAM), and the layers of carbon fiber-reinforced polymer (CFRP) sheets. Test results indicated that the failure mode of CFRP-confined circularized CFSST (C-C-CFSST) columns was similar to that of CFRP-confined concrete columns. The CFRP-confined circularized strengthening method can increase confinement efficacy and reduce the stress concentration at the corners of CFSST columns. Three existing CFRP-confined concrete stress-strain models were evaluated using the test results. The predictions of the Lam and Teng stress-strain model agree well with the test data.